Desiccation- and Saline-Tolerant Bacteria and Archaea in Kalahari Pan Sediments - Genderjahn, Steffi; Alawi, Mashal; Mangelsdorf, Kai; Horn, Fabian; Wagner, Dirk (Frontiers in Microbiology, 2018)
More than 41% of the earth’s land area is covered in permanent or seasonally arid dryland ecosystems. Global development and human activity have led to an increase in aridity, resulting in ecosystem degradation and desertification around the world. The objective of the present work was to investigate and compare the microbial community structure and geochemical characteristics of two geographically allocated saline pan sediments in the Kalahari Desert of southern Africa. Our data suggest that these microbial communities have been shaped by geochemical drivers including water content, salinity, and the supply of organic matter. Using Illumina 16S rRNA gene sequencing, this study provides new insights into the diversity of bacteria and archaea in semi-arid, saline, and low-carbon environments. Many of the observed taxa are halophilic and adapted to water-limiting conditions. The analysis reveals a high relative abundance of halophilic archaea (primarily Halobacteriales), and the bacterial diversity is marked by high abundances of Gemmatimonadetes and spore-forming Firmicutes. In deeper, anoxic layers, candidate division MSBL1 and acetogenic bacteria (Acetothermia) are abundant. Together, the taxonomic information and geochemical data suggest that acetogenesis could be a prevalent form of metabolism in the deep layers of a saline pan.